High Pressure Behaviors and a Novel High-Pressure Phase of Cuprous Oxide Cu2O - Qin, Fei; Zhang, Dongzhou; Qin, Shan (Frontiers in Earth Science, 2021)
In the present study, we extensively explored the phase stabilities and elastic behaviors of Cu2O with elevated pressures up to 29.3 GPa based on single-crystal X-ray diffraction measurements. The structural sequence of Cu2O is different than previously determined. Specifically, we have established that cuprite under pressure, displays a cubic-tetragonal-monoclinic phase transition sequence, and a new monoclinic high-pressure phase assigned to the P1a1 or P12/a1 space group was firstly observed. The monoclinic phase cuprite exhibits anisotropic compression with axial compressibility βb > βc > βa in a ratio of 1.00:1.64:1.45. The obtained isothermal bulk modulus of cubic and monoclinic phase Cu2O are 125(2) and 41(6) GPa, respectively, and the KT0’ is fixed at 4. Our results provide new insights into the phase stability and elastic properties of copper oxides and chalcogenides at extreme conditions.